PENGILMUAN ISLAM KUNTOWIJOYO DAN APLIKASINYA DALAM PENGEMBANGAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM - Fauzi Raharjo, Fajar (STAINU Purworejo, 2018)
This paper informs about the implementation of integration between Islam and science in Islamic Religious Studies in Universities in Indonesia. The development of sciences and technologies which are the effect of desruption era needs the strong spirit to combine between religious knowledge and secular sciences.Thus, Islamic Religious Studies in Universities in Indonesia must be developed. Kuntowijoyo, an Indonesian Muslim intellectual, offered a theory named â€œPengilmuan Islamâ€ orâ€œscientification of Islamâ€. The teory tells that Islam is not against science, but it criticizes and supports. There are two processes to actualize the Scientification of Islam, are integralization and objectification. Integralisation is integrating human sciences with revelation (guidance of Allah in the Qurâ€Ÿan and its implementation in the Sunnah of the Prophet). Objectification is making the Scientification of Islam as a mercy for all people. As the result of the article that the three basics of scientification of Islam can be applied in Islamic Religious learning, and the basics are humanization, liberation and transcendention.The three basic used in every aspect of Islamic religious learning, such as objectives, subject, methods and strategy, and evaluation.This article is the library based paper that use the standar procedur in scientific writing.